Pendampingan Pemeriksaan Gula Darah Kader Simanis Desa Kutuwetan Kecamatan Jetis Ponorogo - Wiwit Suwanto, Agus; Purwaningsih, Endang; Wiratmoko, Heru (Jurnal Empathy Pengabdian Kepada Masyarakat, 2025)
Background: Diabetes mellitus remains a major public health problem in Indonesia due to its high prevalence and risk of severe complications. Health volunteers play a strategic role in primary health care, particularly in early detection and community-based prevention efforts. Strengthening cadres’ skills in blood glucose measurement is essential to support effective screening and health promotion activities. This community service aims to enhance the practical skills of health cadres in performing accurate blood glucose measurements to improve early detection and prevention of diabetes in the community. Methods: The Simanis cadre team from Kutuwetan Village, consisting of 10 members, participated in this community service activity. This community service activity employed a participatory approach through training and direct mentoring. The program involved health volunteers who received theoretical instruction and hands-on practice in blood glucose measurement. Cadre skills were evaluated using pre- and post-training assessments.  Results: The program involved ten health volunteers. The proportion of cadres with good blood glucose measurement skills increased from 83.85% before the intervention to 100% after mentoring, indicating a measurable improvement in cadre competency.  Conclusion: Mentoring-based training effectively improved health volunteers’ skills in blood glucose measurement. It is recommended that cadres apply these skills routinely in community health activities, with periodic re-evaluation every 3–6 months, and that further training be provided on fasting blood glucose and oral glucose tolerance testing to enhance early diabetes detection.